Respuesta :
Answer:
(11/7 , 18/7)
Explanation:
The second given equation is:
y = x + 1 ............> I
The first given equation is:
y = -2.5 x + 6.5 ..............> II
Substitute with I in II and solve for x as follows:
y = -2.5 x + 6.5
x + 1 = -2.5 x + 6.5
x + 2.5 x = 6.5 - 1
3.5 x = 5.5
x = 11/7
Now, substitute with x in equation I to get y as follows:
y = x + 1
y = 11/7 + 1
y = 18/7
Hope this helps :)
(11/7 , 18/7)
Explanation:
The second given equation is:
y = x + 1 ............> I
The first given equation is:
y = -2.5 x + 6.5 ..............> II
Substitute with I in II and solve for x as follows:
y = -2.5 x + 6.5
x + 1 = -2.5 x + 6.5
x + 2.5 x = 6.5 - 1
3.5 x = 5.5
x = 11/7
Now, substitute with x in equation I to get y as follows:
y = x + 1
y = 11/7 + 1
y = 18/7
Hope this helps :)